2019
DOI: 10.1113/ep087493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute nitric oxide precursor intake on peripheral and central fatigue during knee extensions in healthy men

Abstract: New Findings What is the central question of this study?What is the effect of acute NO precursor intake on vascular function, muscle and cerebral oxygenation and peripheral and central neuromuscular fatigue during knee‐extension exercise? What is the main finding and its importance?Acute NO precursor ingestion increases the plasma concentrations of NO precursors (nitrate, arginine and citrulline) and enhances post‐ischaemic vasodilatation, but has no significant effect on muscle and cerebral oxygenation, peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
1
6
1
Order By: Relevance
“…first 18 contractions) was significantly greater for NIT compared to PLA. These results contrast with one study, which reported no significant effect of acute NO 3 − ingestion on indices of central or peripheral fatigue or on time‐to‐task‐failure during intermittent isometric knee extension exercise, 31 but are consistent with another study, which found that 5 days of NO 3 − supplementation reduced the rate of muscle fatigue development and extended the time‐to‐task‐failure during dynamic knee extension exercise 32 . Recent meta‐analyses have highlighted the potential for dietary NO 3 − supplementation to enhance skeletal muscle force or power production during high‐intensity exercise 33,34 .…”
Section: Discussioncontrasting
confidence: 95%
“…first 18 contractions) was significantly greater for NIT compared to PLA. These results contrast with one study, which reported no significant effect of acute NO 3 − ingestion on indices of central or peripheral fatigue or on time‐to‐task‐failure during intermittent isometric knee extension exercise, 31 but are consistent with another study, which found that 5 days of NO 3 − supplementation reduced the rate of muscle fatigue development and extended the time‐to‐task‐failure during dynamic knee extension exercise 32 . Recent meta‐analyses have highlighted the potential for dietary NO 3 − supplementation to enhance skeletal muscle force or power production during high‐intensity exercise 33,34 .…”
Section: Discussioncontrasting
confidence: 95%
“…Since L-citrulline and nitrates can increase NO via distinct parallel pathways, their combination may also work synergistically. Several studies by Le Roux-Mallouf and colleagues have examined the effect of the combination of BRJ/nitrates and L-citrulline on markers of blood flow (i.e., an ischemia-reperfusion test) with some showing an increase in the post-occlusive hemoglobin/oxyhemoglobin response suggesting enhanced vasodilation [ 116 , 117 ] and others showing no effect [ 118 , 119 ]. However, the one study from this group examining the potential synergistic effect showed that BRJ plus L-citrulline was no better than BRJ in isolation for enhancing the thigh ischemia-reperfusion test [ 117 ].…”
Section: Synergistic Effects Of Multiple Precursors On Strength Perfo...mentioning
confidence: 99%
“…Several studies by Le Roux-Mallouf and colleagues have examined the effect of the combination of BRJ/nitrates and L-citrulline on markers of blood flow (i.e., an ischemia-reperfusion test) with some showing an increase in the post-occlusive hemoglobin/oxyhemoglobin response suggesting enhanced vasodilation [ 116 , 117 ] and others showing no effect [ 118 , 119 ]. However, the one study from this group examining the potential synergistic effect showed that BRJ plus L-citrulline was no better than BRJ in isolation for enhancing the thigh ischemia-reperfusion test [ 117 ]. Studies by Le Roux-Mallouf and colleagues also failed to show a significant benefit of the BRJ (520 mg nitrate)/L-citrulline (6 g) combination on isometric knee extension performance [ 117 , 118 ], with the exception of one showing an improvement in maximal knee extensor strength and a trend ( p < 0.10) towards significance in knee extension endurance [ 119 ].…”
Section: Synergistic Effects Of Multiple Precursors On Strength Perfo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The release of NO is of great importance in the human coronary artery since it helps to provide myocardial oxygen demand of the heart during exercise and cardiac pacing [6]. Besides, it prevents cardiovascular diseases such as atherosclerosis and platelet adhesion and aggregation [7,8].…”
Section: Introductionmentioning
confidence: 99%